Natural Resource Management in Depopulated Regions of Serbia—Birth of Rural Brownfields or Final Abandonment - Marko Joksimović (Land)
Numerous research studies have long established the causes and consequences of the depopulation of certain regions in Europe, but it seems that there are no systematic approaches to implementing the policy of managing abandoned areas. Following years of demographic decline in settlements, the 2022 census revealed depopulated clusters in Serbia—regions with 20 or fewer residents or even no inhabitants at all. The areas of depopulated settlements are growing territorially from the south towards the north. This paper adopts a broader interpretation of brownfield land, defining it as any previously used land that is no longer employed for commercial purposes, serving as the theoretical foundation. Although they seem economically hopeless, some depopulated clusters have become the subject of research for the exploitation of mineral resources such as gold, copper, zinc, uranium, lithium and coal. The main problem is that depopulated clusters have acquired an ecological stability that would be disrupted by the opening of mines and massive construction. The changes in land use were analyzed using time series data and a formal database of natural resources from these communities. The primary methodological framework was based on the correlation between population size, utilized areas, and the ecological stability coefficient. This study aimed to explore the relationship between the proportion of arable land within a spatial unit and its depopulation rate while also examining how arable land and mineral resources could influence the potential revitalization of rural wastelands in Serbia’s depopulated areas. The primary findings indicate a significant correlation between population decline and changes in the natural environment of abandoned clusters, as well as the significant potential of clusters as rural brownfields. While it is natural to continue with ecological and green space projects, the current liberal and centralized mining management policy can create major problems for the remaining population.